2018
DOI: 10.1016/j.msec.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Silsesquioxane polymer as a potential scaffold for laryngeal reconstruction

Abstract: Cancer, disease and trauma to the larynx and their treatment can lead to permanent loss of structures critical to voice, breathing and swallowing. Engineered partial or total laryngeal replacements would need to match the ambitious specifications of replicating functionality, outer biocompatibility, and permissiveness for an inner mucosal lining. Here we present porous polyhedral oligomeric silsesquioxane-poly(carbonate urea) urethane (POSS-PCUU) as a potential scaffold for engineering laryngeal tissue. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate laryngeal tissue engineering 85‐87,91,92,94,96,97,198‐306 …”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate laryngeal tissue engineering 85‐87,91,92,94,96,97,198‐306 …”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that these materials may be further modified to include a foamlike internal structure which could have implications towards long-term integration and reduced inflammation in vivo 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although natural biomaterials such as decellularized lung ECM have the benefit of containing organ-specific signaling molecules and can provide architecture that closely mimics the native structure, synthetic materials that can be more readily controlled and manufactured on demand are emerging as a potential alternative. New advanced methods for creating tissue-specific materials for use in airway regeneration studies are emerging that can be used with novel biomaterials which can be further biochemically and biomechanically modified to direct cell behavior ( 32 ). This will be an important area of future investigation.…”
Section: Methodsmentioning
confidence: 99%